"Eastern Tourist": A Review of Images of Russian Consumers in Finnish Media - Olga Gurova; Saara Ratilainen (Journal of Economic Sociology, 2015)
This article, based on discourse analysis of the daily Finnish newspaper Helsingin Sanomat, explores images of Russian tourists as consumers, which are often called in the newspaper “eastern tourists”. The purpose of the research is to study how the images of Russian tourists have been evolved over the years 1990–2013. The article demonstrates that the idea of “eastern tourists” has grown into a significant cultural phenomenon in Finland that is reflected in media discourse. However, images of the “eastern tourists” have transformed: in the 1990s, the media was dominated by the image of a “shuttle trader”, traders usually in the informal economy who travel abroad to purchase consumer goods and personally carry them across the border, avoiding customs and tax inspections. This image has been replaced by the image of a middle-class consumer by the beginning of the 2000s. If the image of “shuttle trader” is more often connected in discourse with social problems which such tourists bring, the middle-class consumer, in turn, is mostly seen in the light of the economic benefits which Finland obtains from such consumers. Consequently, in line with this change, to the newspaper depicts the specifics of Russian tourists’ taste and consumption habits. In general, this research allows us to better understand the discourses that represent the perception of Russian tourists in Finnish society.